Perbaikan Visibilitas pada Citra Berkabut Kawah Gunung Berapi Kelud Menggunakan Color Attenuation Prior - Putra, Oddy Virgantara; Firdaus, Muhammad; Utama, Shoffin Nahwa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Mount Kelud is one of the volcanoes that erupted in 2014. To observe the activity, CCTV has been installed in the crater peak of Mount Kelud. The crater of Mount Kelud emits gases coming from the bottom of the crater. The gas makes CCTV surveillance undisturbed so that the resulting image will have noise. By using dehazing, visibility can be improved so that the resulting image can be seen clearly. The method used for this operation is Color Attenuation Prior. In the early stages, there is a dark channel process that works to turn low-intensity pixels dark. The second step is to estimate the atmospheric light from the dark channel image. This process is almost in parallel with the estimation of the depth map. The fourth step is estimating the transmission map, which functions to transmit low-intensity pixels to high-intensity pixels. The last one is the radiance recovery scene. The results show that the foggy image is successful, and it eliminates the fog effect, thus enhancing the visibility of the image. And from questionnaire results, we got 80 % positive results from all respondents. Further research so that it can be applied directly or in real-time.